Effects of altered photoperiod due to COVID-19 lockdown on pregnant women and their fetuses. (2nd July 2020) - Bagci, S.; Sabir, H.; Müller, A.; Reiter, R.J.
ABSTRACT: Maternal circadian rhythms provide highly important input into the entrainment and programming of fetal and newborn circadian rhythms. The light-dark cycle is an important regulator of the internal biological clock. Even though pregnant women spend a greater part of the day at home during the latter stages of pregnancy, natural light exposure is crucial for the fetus. The current recommended COVID-19 lockdown might dramatically alter normal environmental lighting conditions of pregnant women, resulting in exposure to extremely low levels of natural daylight and high-intensity artificial light sources during both day and night. This article summarizes the potential effects on pregnant woman and their fetuses due to prolonged exposure to altered photoperiod and as consequence altered circadian system, known as chronodisruption, that may result from the COVID-19 lockdown.